Smart Data Pricing - Sen, Soumya Ed.; Joe-Wong, Carlee Ed.; Ha, Sangtae Ed.; Chiang, Mung Ed. (New Jersey : Wiley, 2014)
"As demand for data increases, Smart Data Pricing fills a market void in information on telecommunication economics. The book carefully addresses technical issues and workplace policies, system development and integration, research proposals, and business assessments. With both academic and industrial expertise from a variety of fields, Pricing is a practical and inclusive economics resource"--
"Provides insight on business strategies and initiatives through a diverse collection of perspectives"--
Includes index
Keywords: Telecommunication -- Pricing; Resource Allocation